Five-Year Changes in Community-Level Sport Participation, and the Role of Gender Strategies - Eime, Rochelle; Charity, Melanie; Harvey, Jack; Westerbeek, Hans (Frontiers in Sports and Active Living, 2021)
Background: The rate of participation in community-based sport by boys and men has been double that of girls and women. Contributing to this is the fact that some sports have been traditionally male-only or at least very male-dominated. Aim: The aim of this study was to investigate changes in participation in sport by sex and age across 10 major sports in Australia over a four-year period. In conjunction with the analysis of participation trends, the gender strategies that were developed and implemented during this time are reviewed. Methods: This study encompassed all sport participants registered with one of 10 State Sporting Associations in Victoria, Australia in 2015 and in 2019. Participation rates by region, age and sex were calculated. State sport and health policies relating to female participation in sport were reviewed. Results: There were 749,037 registrations in 2015 and 868,266 in 2019. A comparison between 2015 and 2019 shows increases in participation for women and girls across all age groups (4-84 years), and highest increases for those aged 4 (6.6%) and 5-9 (4.7%). For boys there was a considerable decrease in participation for those aged 5-9 years (-3.8%). Discussion: This study provides evidence that whilst participation in sport is still dominated by males, the gap might be gradually closing and this is in line with recent strategies and investments into sport and wider cultural developments in society. The implications of these findings are discussed.